Production of lightweight concrete from waste tire rubber crumb. Issue 3 (2nd July 2016) - Akinyele, Joseph Olawale; Salim, Ramhadhan Wanjala; Kupolati, Williams Kehinde
Abstract: A lot of research has proposed the use of alternative materials in concrete, one of such material that has gained a lot of attention is the waste tire rubber. In this research, rubber crumb was used to partially replace fine aggregate in concrete at 0, 4, 8, 12, and 16% and represented as M0, M4, M8, M12, and M16, respectively. Sieve analysis was carried out on the rubber crumb and sand, while slump, compressive and tensile test were carried out on the concrete samples. The sieve analysis revealed that both the fine aggregate and rubber crumb are poorly graded. The slump test showed that the concrete losses it consistency as more rubber crumb was added. The 28 days compressive strength showed that there was a general reduction in strength. The work concluded that rubber crumb can be used to replace fine aggregate up to 16%, in lightweight concrete.